Mastoid foramen, mastoid emissary vein and clinical implications in neurosurgery - Hampl, Martin; Kachlik, David; Kikalova, Katerina; Riemer, Roxane; Halaj, Matej; Novak, Vlastimil; Stejskal, Premysl; Vaverka, Miroslav; Hrabalek, Lumir; Krahulik, David; Nanka, Ondrej (Acta neurochirurgica, 2018)
BACKGROUND: Mastoid emissary vein is especially important from the neurosurgical point of view, because it is located in variable number in the area of the occipitomastoid suture and it can become a source of significant bleeding in surgical approaches through the mastoid process, especially in retrosigmoid craniotomy, which is used for approaches to pathologies localized in the cerebellopontine angle. Ideal imaging method for diagnosis of these neglected structures when planning a surgical approach is high-resolution computed tomography. The aim of this work was to provide detailed information about this issue. METHODS: We studied a group of 295 skulls obtained from collections of five anatomy departments and the National Museum. Both quantitative and qualitative parameters of the mastoid foramen were evaluated depending on side of appearance and gender. Individual distances of the mastoid foramen from clearly defined surface landmarks (asterion, apex of mastoid process, foramen magnum) and other anatomical structures closely related to this issue (width of groove for sigmoid sinus, diameters of internal and external openings of mastoid foramen) were statistically processed. RESULTS: The most frequently represented type of the mastoid foramen is type II by Louis (41.2%). The differences between right and left sides were not statistically significant. In men there was a higher number of openings on the right side and in qualitative parameters the type III and IV predominated, whereas in women the types I and II were more frequent. In men, greater distances from the mastoid foramen were observed when evaluating qualitative parameters for defined surface landmarks. Mean size of the external opening diameter was 1.3 mm; however, several openings measured up to 7 mm. CONCLUSIONS: Despite excellent knowledge of anatomy, however, good pre-operative examination using imaging methods and mastering of microsurgical techniques create the base for successful treatment of pathological structures in these anatomically complex areas.
Keywords: pooperační komplikace; Mastoid; kraniotomie; Craniotomy; Jugular Veins; lidé; processus mastoideus; Foramen Magnum; Cerebellopontine Angle; Humans; Postoperative Complications; venae jugulares; foramen magnum; mostomozečkový úhel